2021
DOI: 10.1002/dta.3118
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the enantiomeric composition of amphetamine, methamphetamine and 3,4‐methylendioxy‐N‐methylamphetamine (MDMA) in seized street drug samples from southern Germany

Abstract: Amphetamine (speed), methamphetamine (crystal meth), and 3,4-methylenedioxy-Nmethylamphetamine (MDMA, ecstasy) represent the most frequently abused amphetamine-type stimulants (ATS). Differences in pharmacological potency and metabolism have been shown for the enantiomers of all three stimulants. Legal consequences in cases of drug possession may also differ according to the German law depending on the enantiomeric composition of the seized drug. Therefore, enantioselective monitoring of seized specimens is cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…In-house analysis of real-life samples seized by Austrian police revealed that pure enantiomers of certain products are a result of educts as pure enantiomers, as it is the case for the production of crystal meth from ephedrine available as over-the-counter tablets [16]. These findings also correlate with a recent publication [17].…”
Section: Figure 1 Cathinone Crystals and Tablets Offered In An Online Shopsupporting
confidence: 68%
“…In-house analysis of real-life samples seized by Austrian police revealed that pure enantiomers of certain products are a result of educts as pure enantiomers, as it is the case for the production of crystal meth from ephedrine available as over-the-counter tablets [16]. These findings also correlate with a recent publication [17].…”
Section: Figure 1 Cathinone Crystals and Tablets Offered In An Online Shopsupporting
confidence: 68%
“…Median concentrations of amphetamine were 16.2%, in a range of 0.4 to 73.1%. With respect to the presented case, amphetamine concentrations in secured narcotics in Europe and in the work from Losacker et al [6] were significantly higher compared to the drug concentrations found herein. Hence, the measured concentrations would rather comply with contamination of the syringe, especially on the outlet.…”
Section: Discussioncontrasting
confidence: 56%
“…Referring to the European Drug Report of the EMCDDA [1] from 2020 the averagely found amphetamine concentrations in narcotics in Europe were located between 13 and 67% in 2019, whereby one-half of the countries reported an average purity of 20-35%. In a publication by Losacker et al [6], 79 seizures of amphetamine samples, mostly powders, were investigated. Median concentrations of amphetamine were 16.2%, in a range of 0.4 to 73.1%.…”
Section: Discussionmentioning
confidence: 99%
“…2019 GC/MS method for fenethylline profiling of seized samples ; LC-QTOF-MS method for the simultaneous analysis of 111 amine-based compounds belonging to ergogenics, anorectics and other active components including phenethylamines (amphetamines, ephedrines), sibutramine or yohimbine [ 475 ]; excitation-emission matrix fluorescence combined with parallel factor analysis for quantitative analysis of the ATSs illegal drugs [ 476 ]; 2020 investigation of the efficiency and effectiveness of a gas-to-liquid (GTL) extraction system for the extraction of amphetamine-type substances and their precursors from the vapor phase [ 477 ]; LC-MS/MS method for detection of the presence of synthetic amines in dietary supplements [ 478 ]; enantioselective HPLC-MS/MS method for the quantification of (R)-AMP, (S)-AMP, (R)-MA, (S)-MA, (1R,2R)-pseudoephedrine, (1S,2S)-pseudoephedrine, (1R,2S)-ephedrine, (1S,2R)-ephedrine, (1R,2S)-norephedrine, (1S,2R)-norephedrine, (R)-cathinone, (S)-cathinone, and (1S,2S)-norpseudoephedrine (cathine) [ 479 ]; 2021 review of MA and AMP detection and roadside testing [ 480 ]; determination of the variations in delta C-13 and delta N-15 values of nitrogen sources used in the clandestine production of ATSs using isotope ratio mass spectrometry [ 481 ]; electrochemiluminescence strategy for the screening of MA and AMP [ 482 ]; review of laboratory-based and portable methods for detection of ATSs [ 483 ]; review of the prevalence of ATSs in Iran [ 484 ]; SALDI-MS method for the analysis of ATSs, including MA, MDMA, MDEA, and 4-fluoromethamphetamine (4-FMA) [ 485 ]; ATS drug classification using a one-dimensional convolutional neural network model [ 486 ]; 2022 colorimetric assay for detection of ATSs in aqueous solution, spiked drinks, and ‘ecstasy’ tablets [ 487 ]; development and validation of a GC-MS method for identification and quantification of AMP, MA, MDA and MDMA [ 488 ]; development of drug screening kits for the detection of ATSs in drinks [ 489 ]; analysis of feature selection method for 3D molecular structure of ATS drugs [ 490 ]; study of the pharmacological properties of MDA analogues and two related amphetamine-based compounds (N,alpha-DEPEA and DPIA) detected in street drug samples or in sport supplements [ 491 ]; chiral analysis of AMP (n = 143), MDMA (n = 94), and MA (n = 528) in samples seized in southern Germany in 2019 and 2020 using different chromatographic methods [ 492 ]; comparison of different chiral selectors for the enantiomeric determination of amphetamine-type substances by SPE-CE-MS/MS [ 493 ]; ultrahigh performance LC-MS/MS (UPLC-MS/MS) method coupled with magnetic SPE (MSPE) for determination of ultra-trace ATSs [ 494 ]; desk review of Vietnamese national drug policy documents regarding ATSs and in-depth key informant interviews were conducted from 2019 to 2021 [ 495 …”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%